Kesadaran Sosial Dari Sekolah Menuju Kebangkitan Kembali Wanita Indonesia - Sukasih, Sukasih (Sunan Kalijaga State Islamic University & The Asia Foundation, 2010)
Social consciousness can be from the social science learning by using ways portraying the consciousness of society individuals, culture experience and the development of student personality. By using the consciousness of the personality the students of social science education get values and democracy attitude so that it can develop good citizens. Good citizens have their own responsibility, human rights and the same opportunity between men and women. The social science education to examine social change begins from the accepted postulate that changes constitute inseparable parts in the human Zife constantly. The direct and indirect changes in thought, student attitude towards gender equality constitutes changing process developed through the social science education. The social science education develops the social consciousness of students at schools to the reawakening of Indonesian women in the changing process constantly since the school gets the materials of equality and human rights.